Evaluation of the new marker interleukin - 33 in Iraqi female patients with hyperthyroidism. - Ali, Bushra H. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Hyperthyroidism refers to overactive of thyroid gland leading to excessive synthesis of thyroid hormones and accelerated metabolism in the peripheral tissue.Objective: The aim of this study is to evaluate a new member of the IL-1 super family of cytokines interleukin-33(IL-33) levels in serum .in order to evaluate its utility as clinical bio marker of autoimmune disease (i.e. hyperthyroidism)Methods: The present study was conducted on 30 patients from the Iraqi female patients with hyperthyroidism attending Baghdad teaching hospital, in addition to 30 healthy controls. All subjects were (35-65) years old. Parameters measured in the sera of patients and healthy groups, were interleukin -33 (IL-33), Thyroxin (T4), Thyroxin (T3) and Thyroid stimulating hormone TSH.Results: A new member of super family cytokines Interleukin -33 was determined in hyperthyroidism, female patients. Higher significant elevation was found when compared with healthy control.Conclusion: From this study a conclusion was drawn, that evaluation of concentration of a new super family cytokines IL-33 could consider as a clinical biomarkers in hyperthyroidism female patients. This finding may indicate that autoimmune disease like hyperthyroidism might influence cytokine like interleukin -33 production in these patients